IMPROVING DIGITAL LITERACY FOR AISYIYAH ENTREPRENEURS TO WIN BUSINESS COMPETITION IN THE PANDEMIC PERIOD (SURAKARTA RESIDENCY STUDY) - Dwi Eko Waluyo; Pradana Jati Kusuma; Mochammad Eric S. W. (LP2M STP Mataram, 2022)
Digital literacy training for women entrepreneurs Aisyiyah at the Surakarta Residency provides a series of activities in winning business competition during the pandemic. The purpose of this training to increase digital literacy, to provide knowledge and skills about basic concepts in product planning and marketing, including pricing, product life cycle, utilization of marketing channels and integrated marketing efficiency. The methods used in this training include in-depth interviews, discussions, practicals, and interactive counseling. This training provides by creating an online store and understanding the concept and understanding of building a competitive business and marketing. It is hoped that The Aisyiyah Entrepreneurial School can add insight, ideas, and business opportunities effectively and overcome the obstacles and faced in running a business during the Covid-19 pandemic and also can develop their business so that they can increase their income and welfare and be able to become a sustainable business in the future.